Driving the human ecological footprint. Issue 1 (1st February 2007) - Dietz, Thomas; Rosa, Eugene A.; York, Richard
Abstract : This comparative analysis shows that population size and affluence are the principal drivers of anthropogenic environmental stressors, while other widely postulated drivers (eg urbanization, economic structure, age distribution) have little effect. Similarly, increased education and life expectancy do not increase environmental stressors, suggesting that some aspects of human well‐being can be improved with minimal environmental impact. Projecting to 2015, we suggest that increases in population and affluence will likely expand human impact on the environment by over one‐third. Countering these driving forces would require increases in the efficiency of resource use of about 2% per year.